Misconception Analysis: A Necessary Complement to Investigated the Causes of Students’ Misconception in Conducting Research and Development - Wicaksana, Ervan Johan; Lukman, Aprizal; Siburian, Jodion (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
This study aims to analyze the need for the development of learning books in the form of research and development (R&D) model books to deal with student misconceptions in final project writing. This study analyzes student needs so that practical actions can be found in the early stages of developing research books. The development of R&D books that is carried out is expected to be able to deal with student misconceptions. Errors in understanding R&D are often experienced by students in the mentoring process which emphasizes the end result rather than the development process. The proposed solution is to use misconseption analysis (MA). This type of research is research and development or R&D (research and development) which refers to the ADDIE model with data analysis techniques using descriptive statistics. This stage is the initial stage of ADDIE, namely analysis. Data were obtained from 11 student respondents from a university consisting of three men and eight women. Based on the data collected, the results of student assumptions in understanding development research are not in accordance with actual understanding. The assumption data for students’ understanding of R&D development is 18.18% very understanding, 27.27% understanding, 36.36% quite understanding, 18.18% do not understand. 0.00% don’t understand. Whereas in fact the understanding of students in R&D development is 0.00% very understanding, 9.09% understands, 27.27% understands quite well, 36.36% does not understand, and 27.27% does not understand. The majority of students in research using the R&D method experience misconceptions. The concept that they believed was correct, it turned out that after being studied there were several mistakes or misunderstandings. Students do not get the main source of input in the mentoring process. The misconception is also caused by the fact that in writing a thesis, students have not received references that are studied in depth about the development model.